In vitro digestibility of a pastoral ecotypes collection of Melilotus officinalis - Lahkim Bennani M.; Ayadi M.; Aarab A. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The aim of this study was to determinate the in vitro enzymatic digestibility of twenty ecotypes of yellow sweet clover (Melilotus officinalis) which were collected from the North-West Moroccan pasture. This collection was cultivated in the INRA experimental station in Tangier. The samples were collected during three growth stages of vegetative development. From the vegetative to the flowering stage, the fermentation parameters have also experienced a clear decrease. Indeed, we recorded a very high significant drop (P<0.001) for production of microbial biomass “PMB” (330.84 to 119.17 mg), for partition factor “PF” (4.07 to 2.77 mg/ml), for the speed coefficient of gaz production “c” (0.11 to 0.09 h-1) and for protein digestibility “dE” (49.54% to 26.41% of crude protein “CP”). The gaz production decreased from 216.33 to 179 ml/g in the budding stage and then increased highly to 185.33ml/mg in the flowering stage. The best ecotypes have recoded values of 340.04 mg for PMB, 4.15 mg/ml for PF, 0.11 h-1 for c, 64.86% CP for dE. This study showed that yellow Melilot presents a wide genetic diversity of nutritional parameters that can be exhibited in the field of animal nutrition, essentially in the vegetative stage, which presented interesting nutritional parameters.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)